A Hopkins Chronology - McDermott, J. author. aut Link
XXIII, 161 p.
Keywords: This Hopkins chronology describes the poet's family and early education, then gives a day-by-day account of what he was doing, reading and writing, and the people he met. Drawing on some material not published before, it illustrates the working life of a priest-poet whose work was not made public until more than thirty years after his death. There are additional sections on the religious and political background of a major Victorian writer whose life was essentially enigmatic and private.